Genotoxic evaluation of newly synthesized iminothiazolidinones - Tugcu, Fatma Tulay; Turhan, Kadir; Karadayi, Mehmet; Gulluce, Medine (SAGE PUBLICATIONS INC, 2017)
The current study was designed to assess the potential toxicological effects of newly synthesized iminothiazolidinones by employing Ames Salmonella, Escherichia coli WP2, Zea mays seed germination, and random amplified polymorphic DNA (RAPD) assay systems. The bacterial tester strains S. typhimurium TA1535, TA1537, TA1538, TA98, TA100, and E. coli WP2uvrA were chosen to test the direct gene mutation inducing capabilities of the test materials in prokaryotic systems and Z. mays seeds for determination of potential toxicological effects in eukaryotic systems. OPA-3 and OPA-6 primers were used in the RAPD analysis to determine genotoxic activities on the eukaryotic genomes. According to the results, none of the test materials showed significant mutagenic activity on the bacterial tester strains at the chosen concentrations. Additionally, none of the tested compounds showed inhibition of the germination of Z. mays seeds. In contrast, the RAPD analysis results were inconsistent with the bacterial reversion assays and the seed germination assay results. All test materials significantly changed the RAPD profiles for OPA-3; however, only compound 5 showed a significant change for OPA-6 when compared with the control groups. In conclusion, the newly synthesized iminothiazolidinone derivatives (C1-C5) were determined as potentially genotoxic compounds and they should be checked with multiple toxicology test systems before further studies to determine their actual use.
Keywords: Iminothiazolidinones; Ames Salmonella assay; E. coli WP2 assay; Z. mays seed germination; RAPD; NITRO-N-NITROSOGUANIDINE; EASTERN ANATOLIA REGION; ONE-POT SYNTHESIS; MUTAGENICITY ASSAY; SODIUM-AZIDE; COLI WP2; E. COLI; TURKEY; 9-AMINOACRIDINE; Public, Environmental & Occupational Health; Toxicology